2005
DOI: 10.1590/s0100-879x2005000400015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of melatonin on the development of functional nicotinic acetylcholine receptors in cultured chick retinal cells

Abstract: The influence of melatonin on the developmental pattern of functional nicotinic acetylcholine receptors was investigated in embryonic 8-day-old chick retinal cells in culture. The functional response to acetylcholine was measured in cultured retina cells by microphysiometry. The maximal functional response to acetylcholine increased 2.7 times between the 4th and 5th day in vitro (DIV4, DIV5), while the Bmax value for [ 125 I]-α-bungarotoxin was reduced. Despite the presence of α8-like immunoreactivity at DIV4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…The mRNA of the immature MT 1 receptor already was showed in undifferentiated 2 days neural stem cells in culture (Niles et al, 2004). The blockage by luzindole of the α‐bungarotoxin acetylcholine receptor appearing occurred only in completely differentiated cells cultivated for at least 5 days (Sampaio et al, 2005). The absence of the luzindole effect also was shown occurring in Chinese hamster ovary cells expressing MT 1 melatonin receptor (Witt‐Enderby and Dubocovich, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mRNA of the immature MT 1 receptor already was showed in undifferentiated 2 days neural stem cells in culture (Niles et al, 2004). The blockage by luzindole of the α‐bungarotoxin acetylcholine receptor appearing occurred only in completely differentiated cells cultivated for at least 5 days (Sampaio et al, 2005). The absence of the luzindole effect also was shown occurring in Chinese hamster ovary cells expressing MT 1 melatonin receptor (Witt‐Enderby and Dubocovich, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA of the Mel 1a , Mel 1b and Mel 1c were located throughout the cellular layers, comprising the photoreceptors layer, the inner nuclear layer and the ganglion cell layer (Natesan and Cassone, 2002). These receptors can be pharmacologically identified in the retina and other tissues by luzindole ( N ‐acetyl‐2‐benziltryptamine), an antagonist/inverse agonist of the melatonin receptors (Dubocovich et al, 2003; Sampaio et al, 2005), and 4‐P‐PDOT (4‐phenyl‐2‐propionamidotetralin), a competitive antagonist capable of differing MT 2 from other melatonin receptors (Markowska et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…At the embryonic days studied, the melatonin inhibitory effect is not blocked via the melatonin receptor unselective antagonist luzindole (Sampaio, 2008). The same absence of luzindole antagonist activity is observed in melatonin modulator effect on α‐bungarotoxin‐sensitive nicotinic acetylcholine receptors expression in partly differentiated retinal cells cultures (Sampaio et al, 2005). This finding is interesting because the classical luzindole antagonist effect is well known on both melatonin inhibition of the cAMP levels and α‐bungarotoxin‐sensitive nicotinic acetylcholine receptors appearing in differentiated retinal neurons in culture (Iuvone and Gan, 1994; Sampaio et al, 2005).…”
Section: Methodsmentioning
confidence: 61%
“…The same absence of luzindole antagonist activity is observed in melatonin modulator effect on α‐bungarotoxin‐sensitive nicotinic acetylcholine receptors expression in partly differentiated retinal cells cultures (Sampaio et al, 2005). This finding is interesting because the classical luzindole antagonist effect is well known on both melatonin inhibition of the cAMP levels and α‐bungarotoxin‐sensitive nicotinic acetylcholine receptors appearing in differentiated retinal neurons in culture (Iuvone and Gan, 1994; Sampaio et al, 2005). With this paper, we show that 5‐MCA‐NAT induces increase in cAMP levels in chick retinas, beginning in the precocious stages of neurodevelopment and that luzindole blocks this effect.…”
Section: Methodsmentioning
confidence: 61%
“…We have previously shown that melatonin modulates α7 nAChR in fibers of rat skeletal muscle in culture (Almeida‐Paula et al, 2005), in rat sympathetic nerve terminals (Carneiro et al, 1991; Markus et al, 1996; Zago and Markus, 1999) and in rat cerebellar slices (Markus et al, 2003). Melatonin also modulates functional α8 nAChR appearing in the development of chick retinal cells in culture (Sampaio et al, 2005).…”
Section: Methodsmentioning
confidence: 99%